Quantitative detection and genetic characterization of thermotolerant Campylobacter spp. in fresh chicken meats at retail in Japan - Asakura, Hiroshi; Yamamoto, Shiori; Yamada, Kazuhiro; Kawase, Jun; Nakamura, Hiromi; Abe, Kou-ichiro; Sasaki, Yoshimasa; Ikeda, Tetsuya; Nomoto, Ryohei (Frontiers in Microbiology, 2022)
Campylobacter jejuni and C. coli are one of the leading causes of gastrointestinal illnesses, and which are considered to be transmitted to humans mainly from chicken meats. Considering the less availability of quantitative contamination data in the retail chicken meats in Japan, 510 fresh chicken meats retailed at five distinct regions in Japan between June 2019 and March 2021 were examined. The quantitative testing resulted that 45.7% of the samples (254/510) were positive at mean±standard deviation of 1.15±1.03 logCFU/g, whereas 43 samples (8.4%) exceeded 3.0 logCFU/g. Seasonal comparison revealed increased bacterial counts in fall compared with spring and summer. As for the chicken slaughter age, those slaughtered at >75 days old were less contaminated than those at <75 days old. Genome sequencing analyses of 111 representative C. jejuni isolates resulted in the detection of three antimicrobial resistance genes (gyrA substitution T86I, tetO and blaOXA-61) at 25.2%, 27.9% and 42.3%, respectively. In silico MLST analysis revealed the predominance of sequence types (ST)-21 clonal complex (CC), followed by ST-45CC and ST-464CC. The single nucleotide polymorphism (SNP)-based phylogenetic tree largely classified the sequenced C. jejuni isolates into two clusters (I and II), where all C. jejuni from highly contaminated samples (STs-21CC, -22CC and -45CC) belonged to cluster I, independent of both season and slaughter age. To our knowledge, this is the first example to study the current status of Campylobacter contamination levels in fresh chicken meats retailed in Japan. Our data would be contributable to future quantitative microbial risk assessment, to establish effective control measures for campylobacteriosis.